2021
DOI: 10.3390/ma14237203
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Response and Failure Analysis of Solid and Hollow Core Concrete Beams with Additional Opening at Different Locations

Abstract: It is essential to make openings in structural concrete elements to accommodate mechanical and electrical needs. To study the effect of these openings on the performance of reinforced concrete (RC) elements, a numerical investigation was performed and validated using previous experimental work. The effect of the position and dimension of the opening and the beam length on the response of the beams, loads capacities, and failure modes was studied. The simulated RC beams showed different responses, loads capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In this regard, the results obtained by us in the design characteristics, which do not affect the change in concrete along the height of the variotropic section, compare favorably in the direction of acquiring advantages in relation to works such as [ 1 , 2 , 3 , 4 , 5 , 6 ]. Further, it should be noted that, in the aspect of comparing the approach to the differentiation of concrete over the section of the element, the work was performed for the first time and correlates only with studies [ 77 , 78 ], which were taken as the basis for numerical experiments.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…In this regard, the results obtained by us in the design characteristics, which do not affect the change in concrete along the height of the variotropic section, compare favorably in the direction of acquiring advantages in relation to works such as [ 1 , 2 , 3 , 4 , 5 , 6 ]. Further, it should be noted that, in the aspect of comparing the approach to the differentiation of concrete over the section of the element, the work was performed for the first time and correlates only with studies [ 77 , 78 ], which were taken as the basis for numerical experiments.…”
Section: Resultsmentioning
confidence: 77%
“…This is in contrast to [ 3 ], where, due to activation by electric heating, the deflection of the bending elements increased. In [ 6 ], the deflection of reinforced concrete beams was regulated using additional holes in different places of solid and hollow elements. In this case, an increase in beam deflection was also observed [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In higherstrength concrete, beam brittle failure is caused by shear force and the development of a diagonal crack. The different types of openings reduce the stiffness of reinforced cement concrete (RCC) beams [8]. Dong et al (2002) [9] suggested that the load carrying capacity and stiffness of pre-cracked RC beams can be increased by providing carbon fiber-reinforced polymer (CFRP) at the tension side of the beam; the failure of the concrete cover and the debonding between the CFRP fabric and the concrete should also be investigated.…”
Section: Introductionmentioning
confidence: 99%